Investigating Joint Replenishment Inventory Models - Shumnij, Joonnajak (2010)
The purpose of this project is to explore the usefulness of joint replenishment inventory model on a soft drinks company and their major wholesalers. In order to investigate the performance of joint replenishment, the simulation of the inventory system is performed for three different models including the EOQ model, adjusted EOQ model, and joint replenishment inventory model. In this study, the approach taken is quantitative due to the fact that linear programming and spreadsheet are used extensively throughout the project.